A Spectrum of Histopathological Findings in Hysterectomy Specimens at a Tertiary Care Center in Western Nepal: A Descriptive Study - Lama, Laxmi; Karki, Asmita; Khanal, Anupa; Shrestha, Dipesh; Vaidya, Sahesh Gopal; Bajracharya, Prasamsha; Khatri, Swostika (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Hysterectomy is a widely performed major surgical procedure in women globally. It is performed as a definitive treatment for several pathologies of female reproductive organs, which include uterine fibroids, uterine prolapse, abnormal uterine bleeding, adenomyosis, endometriosis, and malignancies. The current study aimed to assess the spectrum of histopathological findings in hysterectomy specimens. Methods: A retrospective descriptive study was conducted in the Department of Pathology from November 2022 to July 2025 after ethical approval from the Institutional Review Committee. (Reference number: IRC-LMC-07/2025) A total of 210 women were enrolled who presented with a clinical diagnosis of female genital tract lesions. Clinical details, including age of patients, preoperative diagnosis and type of surgical procedure, were retrieved from medical records of the Department of Obstetrics and Gynaecology. All slides were observed under a light microscope by the consultant pathologist. Descriptive data were analyzed statistically, and SPSS software version 25 was used for the analysis. Results: Among the specimens observed, the most predominant endometrial lesions were proliferative phase endometrium in 103 (49%) cases, followed by atrophic endometrium in 51 (24.28%) cases. Leiomyoma was the most common myometrial lesion in 90 (42.85%) cases, and adenomyosis was seen in 20 (9.52%). The ovaries manifested various lesions; the corpus luteal cyst was the most frequently encountered lesion, seen in 23 (16.31%) cases and two malignant tumors one high-grade serous carcinoma and one transformed teratoma. Conclusions: The current study revealed that a wide spectrum of lesions can be identified on histopathological examination. Therefore, it is essential that all hysterectomy specimens undergo thorough histopathological evaluation even when they appear grossly normal.